KEY APPROACHES OF LIFE-CYCLE COST IN GREEN GOVERNMENT PROCUREMENT (GGP) FOR GREEN PROJECTS - Khalil, Natasha; Mohamad Bohari, Asmah Alia; Shamsudin, Siti Mazzuana; Abd Rashid, Ahmad Faiz; Husin, Husrul Nizam (PLANNING MALAYSIA, 2021)
Sustainability has emerged as a critical concern in any viable physical planning and development. Hence, the Malaysian government has promoted the concept of green procurement also known as Government Green Procurement (GGP) that aims to minimize environmental degradation. In GGP, life cycle perspective thinking is introduced where life-cycle cost (LCC) tools act as decision-making in controlling the initial and future value of building ownership. Despite the increasing importance of green procurement and LCC in the planning phase of green projects, the viability and implementation of LCC is still lacking. Many have stated the benefits of LCC in green procurement for green building projects, however the criteria of LCC are not clearly determined. The study aims to determine the important level of LCC components relating to the green project planning phase. Questionnaire survey was distributed to 50 respondents composed of project team members that were involved in the selected green government projects. 32 respondents returned their responses to the survey. The results revealed that the highest rank of LCC components in green procurement is energy consumption cost, greenhouse gas (GHG) savings cost, acquisition cost, energy simulation cost and utilities cost. These results would elevate the use of LCC in the green procurement adoption and viability of green projects.